Trilateral Relation between Nepal, India and China - Acharya, Madhukar Mani (NPRC Journal of Multidisciplinary Research, 2026)
Background: Nepal lies in a highly strategic location between two major Asian powers, India and China. Because of its geography, historical relationships, and economic linkages with both neighbors, Nepal has always been an important point of interest in regional politics. In recent years, China’s growing presence in South Asia and Nepal’s long-standing close ties with India have made the idea of trilateral cooperation both relevant and complex. Methods: This study uses a qualitative and descriptive approach based on secondary sources. Information has been gathered from books, journal articles, policy papers, treaties, and other scholarly works related to Nepal’s foreign policy and its relations with India and China. A comparative and analytical method is applied to understand the political, economic, and strategic dimensions of these relationships. Results: The findings show that there is strong potential for cooperation among Nepal, India, and China, especially in areas like trade, infrastructure development, hydropower, tourism, and regional connectivity. However, this potential is limited by ongoing border issues, strategic mistrust, and geopolitical competition between India and China. Nepal continues to follow a balancing foreign policy to maintain good relations with both neighbors while protecting its sovereignty and national interests. Among all sectors, economic cooperation appears to be the most practical and achievable area for trilateral engagement. Conclusion: Trilateral cooperation among Nepal, India, and China can contribute to peace, stability, and economic development in the region. For this to happen, stronger political trust, regular dialogue, and mutual respect are necessary. Nepal’s balanced diplomatic approach is essential in maintaining stability in this sensitive regional environment. Novelty: This study brings together geopolitical, economic, and security perspectives to provide a clear understanding of Nepal’s role as a bridge between India and China, highlighting both opportunities and challenges in trilateral relations.